2010
DOI: 10.1007/s10722-010-9576-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Arachis based on internal transcribed spacer sequences

Abstract: Phylogenetic analysis, based on nuclear rDNA internal transcribed spacers (ITS) of Arachis species, corroborated a broad sub-classification of the genus. Three clustering algorithms were used to generate dendrograms which showed that Arachis Sections Extranervosae, Heteranthae and Triseminata were most primitive, and Section Arachis was most advanced, with Sections Caulorrhizae, Erectoides, Procumbentes, Rhizomatosae, and Trierectoides intermediate in evolutionary terms, in relation to the genus Stylosanthes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…A study of ITS and rDNA also produced a clade containing species from the taxonomic sections Procumbentes, Rhizomatosae, Erectoides, and Trierectoides joined with species from section Arachis (Bechara et al 2010). The reconstruction of phylogenetic relationships from previous studies (Friend et al 2010;Bechara et al 2010;Wang et al 2011) and this study based on DNA sequences show this divergent clade/group, and detailed genome affinity of species within this group needs further investigation using additional genic sequences representing different genome regions to help resolve their relationships.…”
Section: Phylogeny Of Species Of Arachis Of All Nine Sectionsmentioning
confidence: 66%
See 2 more Smart Citations
“…A study of ITS and rDNA also produced a clade containing species from the taxonomic sections Procumbentes, Rhizomatosae, Erectoides, and Trierectoides joined with species from section Arachis (Bechara et al 2010). The reconstruction of phylogenetic relationships from previous studies (Friend et al 2010;Bechara et al 2010;Wang et al 2011) and this study based on DNA sequences show this divergent clade/group, and detailed genome affinity of species within this group needs further investigation using additional genic sequences representing different genome regions to help resolve their relationships.…”
Section: Phylogeny Of Species Of Arachis Of All Nine Sectionsmentioning
confidence: 66%
“…Although A. dardani and A. retusa were alternatively at the base when using different genic sequences, the phylogenetic tree based on combined genic sequences of seven loci generated strong support for the basal clade. Species from section Extranervosae were also depicted as one of two terminal lineages in the studies of Friend et al 2010 andWang et al 2011 because they used several species from section Extranervosae and the same DNA sequences. We used only one species, A. retusa, from section Extranervosae, which was absent in their studies, making a slight difference for the basal clade in our study.…”
Section: Phylogeny Of Species Of Arachis Of All Nine Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…& W.C. Gregory (Robledo and Seijo, 2010). This new classification is supported by systematic molecular studies on the genus Arachis (Bechara et al, 2010;Friend et al, 2010;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 74%
“…On the other hand, PCR amplified fragment length polymorphism (AFLP) data have shown that at least three diploid species with the A genome and three with the non-A genome have small genetic distance compared with the cultigen whereas microsatellite markers have revealed that, although A. duranensis and A. ipae¨nsis are closely related to the cultigen, a small group of other species having the A or non-A genomes could also be possible genome donors (Moretzsohn et al 2004). Likewise, the inferences made on the relationships between the allopolyploids (A. monticola and peanut) and between them and the wild diploid species using ITS and 5.8 rDNA sequences are limited, because of the polytomies obtained in the dendrograms (Friend et al 2010;Bechara et al 2010;Wang et al 2010). Those interpretations were also hampered because the sequences obtained from the tetraploids could have represented only one of the genomes or may have even been a mixture of the sequences from both genomes, as pointed out by Bechara et al (2010).…”
Section: Introductionmentioning
confidence: 99%